Inquiry-Based Learning as a Strategy to Enhance Expository Writing - Siti Nurfadhilah Gani; Munir; La Sunra (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study aims to examine the effectiveness of the Inquiry-Based Learning approach in teaching expository writing at the secondary school level. A quantitative method was employed, utilizing a pre-experimental design that involved administering pre-tests and post-tests. Student essay scores obtained from pre- and post-tests were analyzed using the Wilcoxon Signed-Rank Test due to the non-normal distribution of the data. The findings showed a statistically significant improvement in writing ability, reflected in a Z-score of -4.534 and a significance level of 0.005 (p < 0.01), indicating that the Inquiry-Based Learning approach had a statistically significant impact on writing achievement. This approach has been demonstrated to promote active student engagement in exploration, problem-solving, and reflection, which significantly contributes to the enhancement of writing quality, particularly in terms of argumentation, coherence, and logical structure. These results affirm the pedagogical value of Inquiry-Based Learning in developing academic literacy skills, particularly in expository writing.